Resistance mutations that distinguish HIV-1 envelopes with discordant VRC01 phenotypes from multi-lineage infections in the HVTN703/HPTN081 trial: implications for cross-resistance - Paula Cohen; Bronwen E. Lambson; Nonhlanhla N. Mkhize; Chivonne Moodley; Anna E. J. Yssel; Thandeka Moyo-Gwete; Talita York; Asanda Gwashu-Nyangiwe; Nonkululeko Ndabambi; Ruwayhida Thebus; Michal Juraska; Allan C. deCamp; et al. (Journal of Virology, 2025)
ABSTRACT The Antibody Mediated Prevention (AMP) trials showed that passively infused VRC01, a broadly neutralizing antibody (bNAb) targeting the CD4 binding site (CD4bs) on the HIV-1 envelope protein (Env), protected against neutralization-sensitive viruses. We identified six individuals from the VRC01 treatment arm with multi-lineage breakthrough HIV-1 infections from HVTN703, where one variant was sensitive to VRC01 (IC50 < 25 ug/mL) but another was resistant. By comparing Env sequences of resistant and sensitive clones from each participant, we identified sites predicted to affect VRC01 neutralization and assessed the effect of their reversion in the VRC01-resistant clone on neutralization sensitivity. In four pairs, a single mutation restored partial or full sensitivity to VRC01, whereas in the fifth participant, transfer of the entire [Formula: see text]23-V5 loop was required. No VRC01 resistance mutations could be identified in the sixth participant, with the discordant clones differing by >100 amino acids. Mutations responsible for the differential neutralization phenotypes occurred at distinct sites across Env, including residues in loop D, the CD4-binding loop, and between the [Formula: see text]23 and V5 loops. Analysis of deep sequencing env data showed that VRC01 resistance was likely the property of the acquired virus, rather than occurring through post-acquisition evolution. Although VRC01-resistant parental clones generally retained sensitivity to other CD4-binding site bNAbs, they were less potently neutralized than the VRC01-sensitive clones. In conclusion, VRC01 resistance mutations occurred through multiple mutational pathways, but sensitivity to second-generation CD4bs bNAbs was retained even in VRC01-resistant transmitted viruses, confirming the potential of these bNAbs for HIV-1 prevention studies.IMPORTANCEThe Antibody Mediated Prevention (AMP) trials provided proof of principle that VRC01, a CD4-binding site (CD4bs) HIV-1 broadly neutralizing antibody (bNAb), prevented the acquisition of antibody-sensitive viruses. However, understanding common mutations that confer resistance to different bNAbs provides important insights into the genetic barrier to resistance. Here we studied six AMP trial participants with breakthrough infections mediated by multiple viral lineages with discordant VRC01 sensitivity. We identified different mutations across the CD4-binding site that conferred resistance to VRC01 and showed that these mutations were a property of the acquired virus, rather than a result of post-acquisition evolution. We found that although VRC01 resistance was associated with reduced neutralization potency of second-generation CD4-binding site bNAbs, overall neutralization sensitivity was generally retained, which is promising for future use of such bNAbs in clinical trials.